Desempenho de soja orgânica com uso de trichoderma harzianum e condicionador de solo - Souza, Maiara Secco de (2020)
Organic soy production has grown in recent years as a need for society to improve eating habits, in addition to reducing the use of pesticides. In conventional cultivation, chemical treatments are commonly used practices, as they help to control pathogens and guarantee the quality of production even in times of stress. However, for organic products, this type of treatment cannot be used, so it is necessary to seek natural forms through the use of biological and alternative products. The objective of the work was to evaluate the effect of Trichoderma harzianum and soil conditioner in the treatment of seeds and in the sowing furrow in the cultivation of organic soy. The work was conducted at the Didactic Laboratory of Seed Analysis and Experimental Area of the Federal Technological University of Paraná - UTFPR, Campus Dois Vizinhos. The commercial biological product Trichoderma harzianum ECOTRICH [marca registrada] and a soil conditioner based on humic and fulvic acids (Lottus SH-24 - Biosolutions) were tested in the treatment of soybean seeds (Experiment 1) and in the application in sowing furrows (Experiment 2). The following explanatory variables were evaluated: moisture content, 1000-seed weight and mechanical damage were evaluated. For the evaluation of the physiological quality of the seeds submitted to the treatment, the variables response in the laboratory were evaluated: germination, length of aerial part and root, dry matter mass, emergency speed index, emergency speed, emergency and emergency speed coefficient accumulated. In addition, plant height, root size, green root mass, nodulation, number of grains per pod, number of pods per plant and productivity were evaluated in the field after application of the products in the sowing furrow. For experiment 1, a completely randomized experimental design (DIC) was used and for experiment 2, a randomized block design (DBC) was used, with four replications, with treatments arranged in a unifatorial scheme. The application of Trichoderma harzianum and humic and fulvic acids in seed treatment improves seedling development in some physiological variables, without negatively influencing any of the evaluations performed. The application of Trichoderma harzianum and humic and fulvic acids favor agronomic variables of the crop, influencing the size of plants, number of pods per plant, number of grains per pod and productivity. Trichoderma harzianum + humic and fulvic acids are compatible and can be applied in the treatment of seeds and sowing furrows in soybean.